A multi-stage game model for the false data injection attack from attacker's perspective. (December 2021) - Yi, Na; Wang, Qi; Yan, Limei; Tang, Yi; Xu, Jianjun
Abstract: With the rapid development and widespread application of information and communication technology, power system has gradually become a cyber physical power system (CPPS) in which the cyber space and physical space are deeply coupled. The continuous interaction between information flow and power flow renders power grid confronted with potential cyber attack risks. As a typical attack approach, false data injection attack (FDIA) interferes with control decisions making by weakening information integrity. In this paper, regarding the phasor measurement unit (PMU) as the attack-defense target in power system, a multi-stage game model for FDIA is proposed based on attacker's perspective, putting particular emphasis on data tampering, strategic adjustments, and multi-path attacks in a multi-stage game. Firstly, from the perspective of the attacker, the false data is constructed based on the PMU configuration, the attack range is optimized, and the attack consequences are quantified. Secondly, based on two-player zero-sum game theory, take the overall revenue and multi-path attacks in multi-stage game into consideration, the optimal attack-defense strategy is obtained by solving the Nash equilibrium point. Finally, experiment results of multi-stage game and one-stage game are discussed. The simulation results demonstrate that the proposed multi-stage game strategy owns better effect and applicability for attackers. Highlights: The false data, attack range and results are analyzed from attacker's perspective. A multi-stage game model is proposed based on two-person zero-sum game theory. The strategic adjustments and multi-path attacks are emphasised in multi-stage game.